Trade Deficits in the Baltic States: How Long Will the Party Last? - Rudolfs Bems; Kristian Jönsson (Sveriges Riksbank, 2005)
Since their opening up to international capital markets, the economies of Estonia, Latvia and Lithuania have experienced large and persistent capital inflows and trade deficits. This paper investigates whether a calibrated two-sector neoclassical growth model can explain the magnitudes and the timing of the trade flows in the Baltic countries. The model is calibrated for each of the three countries, which we simulate as small closed economies that suddenly open up to international trade and capital flows. The results show that the model can account for the observed magnitudes of the trade deficits in the 1995-2001 period. Introducing a real interest rate risk premium in the model increases its explanatory power. The model indicates that trade balances will turn positive in the Baltic states around 2010.
Keywords: C68; F41; 330; Baltic states; international factor movements; non-traded goods; adjustment costs; dynamic general equilibrium